+0  
 
0
249
1
avatar

3x^2-4x+8=8x^2-5x-3

Guest Aug 23, 2017
 #1
avatar+7387 
0

3x^2-4x+8=8x^2-5x-3

 

\(3x^2-4x+8=8x^2-5x-3\\ 4x^2-x-11=0\)    8 - 3 = 5  not  4 !!

a        b       c

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

\(x = {1 \pm \sqrt{1-4\cdot 4\cdot (-11)} \over 2\cdot 4}\)

\(x=\frac{1\pm \sqrt{177}}{8}=0.125\pm 1.6630168\)

 

\(x_1=1.7880168\\ x_2=-1.5380168\)

 

This result is correct for (\(4x^2-x-11=0\)),

but not for (\(3x^2-4x+8=8x^2-5x-3\)).

Why ?

8 - 3 = 5     not  4 !!

Thanks for the help Alan and heureka!
I will correct immediately.

\(3x^2-4x+8=8x^2-5x-3\\ 5x^2-x-11=0\)

a        b       c

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

\(x = {1 \pm \sqrt{1-4\cdot 5\cdot (-11)} \over 2\cdot 5}\)

\(x=\frac{1\pm\sqrt{221}}{10}=0.1\pm 1.48660687 \)

 

\(x_1=1,58660687\)

\(x_2=-1.38660687\)

 

laugh  !

asinus  Aug 23, 2017
edited by asinus  Aug 23, 2017
edited by asinus  Aug 23, 2017
edited by asinus  Aug 23, 2017

11 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.